Food restriction increase the expression of mTORC1 complex genes in the skeletal muscle of juvenile pacu (Piaractus mesopotamicus) - Paula, Tassiana Gutierrez de [UNESP]; Thomazini Zanella, Bruna Tereza [UNESP]; Almeida Fantinatti, Bruno Evaristo de [UNESP]; Moraes, Leonardo Nazario de [UNESP]; Silva Duran, Bruno Oliveira da [UNESP]; Oliveira, Caroline Bredariol de [UNESP]; Simoes Salomao, Rondinelle Artur [UNESP]; Silva, Rafaela Nunes da [UNESP]; Padovani, Carlos Roberto [UNESP]; Santos, Vander Bruno dos; Mareco, Edson Assuncao; Carvalho, Robson Francisco [UNESP]; et al. (Public Library Science, 2017)
Skeletal muscle is capable of phenotypic adaptation to environmental factors, such as nutrient availability, by altering the balance between muscle catabolism and anabolism that in turn coordinates muscle growth. Small noncoding RNAs, known as microRNAs (miRNAs), repress the expression of target mRNAs, and many studies have demonstrated that miRNAs regulate the mRNAs of catabolic and anabolic genes. We evaluated muscle morphology, gene expression of components involved in catabolism, anabolism and energetic metabolism and miRNAs expression in both the fast and slow muscle of juvenile pacu (Piaractus mesopotamicus) during food restriction and refeeding. Our analysis revealed that short periods of food restriction followed by refeeding predominantly affected fast muscle, with changes in muscle fiber diameter and miRNAs expression. There was an increase in the mRNA levels of catabolic pathways components (FBXO25, ATG12, BCL2) and energetic metabolism-related genes (PGC1 alpha and SDHA), together with a decrease in PPAR beta/delta mRNA levels. Interestingly, an increase in mRNA levels of anabolic genes (PI3K and mTORC1 complex: mTOR, mLST8 and RAPTOR) was also observed during food restriction. After refeeding, muscle morphology showed similar patterns of the control group; the majority of genes were slightly up-or down-regulated in fast and slow muscle, respectively; the levels of all miRNAs increased in fast muscle and some of them decreased in slow muscle. Our findings demonstrated that a short period of food restriction in juvenile pacu had a considerable impact on fast muscle, increasing the expression of anabolic (PI3K and mTORC1 complex: mTOR, mLST8 and RAPTOR) and energetic metabolism genes. The miRNAs (miR-1, miR-206, miR-199 and miR-23a) were more expressed during refeeding and while their target genes (IGF-1, mTOR, PGC1 alpha and MAFbx), presented a decreased expression. The alterations in mTORC1 complex observed during fasting may have influenced the rates of protein synthesis by using amino acids from protein degradation as an alternative mechanism to preserve muscle phenotype and metabolic demand maintenance.